Economic Development of Nanotechnology: A Review of Indicators - Angela Hullman (Foresight and STI Governance)
The review examines the current state and prospects of development of nanoindustry. It is based on available statistics and forecasts for markets, companies, financial issues, patents and scientific publications related to nanotechnology developments. The most promising areas are revealed. The contribution of nanotechnology to the achievement of EU’s economic and social objectives is discussed. Attention is given to the comparison of EU’s nanoindustry potential with its major competitors - U.S., Japan and emerging nano powers: China, India and Russia.